A Metastasis‐Tumour‐Like Pulmonary Langerhans Cell Histiocytosis With Association to Positron Emission Tomography/Computed Tomography Finding Confirmed With Surgical Resection - Tzu‐Yi Chuang; Kuo‐Sheng Liao; Yei‐San Hsie; Shih‐Wei Lee (Respirology Case Reports)
ABSTRACT Despite positron emission tomography/computed tomography being a powerful evaluation for recurrence of lung cancer, surgical biopsy may still be necessary to confirm the differential diagnosis of Langerhans Cell histiocytosis.